PERAN ARSIP DALAM PELESTARIAN CAGAR BUDAYA DI INDONESIA: SISTEMATIKA REVIEW - Fidan Safira (Lembaga Ilmu Pengetahuan Indonesia, 2020)
Archives have an important role in the preservation of cultural heritage buildings by the form of information about the history and development of cultural heritage buildings. Archives of heritage buildings are dynamic archives that are vital. Management thus must take priority. This study aims to the use of archives in the preservation of cultural heritage in Indonesia. A systematic review method was used with a qualitative approach. Collection data methods were conducted by planning, implementation, and reporting. The findings showed there are only two articles that review the archives in preservation heritage. Furthermore, our challenge is the lack of cultural heritage documents that most archives used were under regulations on the preservation of cultural heritage. Almost all articles thus showed a preservation model on physical forms and cultural heritage buildings.